Combination of sorafenib and cytokine-induced killer cells in metastatic renal cell carcinoma: a potential regimen. (June 2017) - Yang, Yonghao; Lin, Hongwei; Zhao, Lingdi; Song, Yongping; Gao, Quanli
Metastatic renal cell carcinoma (MRCC) exhibits primary resistance to both chemotherapy and radiotherapy. As an immunogenic cancer, MRCC is relatively sensitive to immunotherapy such as that with cytokines, immune checkpoint inhibitors and adoptive T-cell therapy. In addition, many targeted agents developed over the past decade exhibit greater efficacy than cytokines and have become the standard first-line therapy for MRCC. Several preclinical studies have shown that the targeted agent sorafenib possesses an immunomodulation function and may be suitable for combination with immunotherapy. Here, combinatorial therapy consisting of sorafenib and cytokine-induced killer cell immunotherapy was administered to an MRCC patient resulting in a synergistic effect without serious adverse effects. These results suggest a potential combinatorial regimen for MRCC patients.